Penguatan Literasi Hukum Masyarakat: Perlindungan Korban Cyberbullying Berbasis Hukum Positif dan Hukum Pidana Islam - Zaima Thifal Naika Br. Gultom; Aminah Aminah; Muhammad Alwin Abdillah; Rasyidin Rasyidin (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Langsa, 2026)
This community service program aimed to enhance community legal literacy regarding the legal protection of cyberbullying victims based on Indonesian positive law and the perspective of Islamic criminal law, while identifying the need for legal assistance for victims in Kampung Durian, Rantau District, Aceh Tamiang Regency, Indonesia. The program employed a participatory educational approach through legal awareness seminars, interactive discussions, legal consultation, and evaluation involving 35 participants, including community members, village officials, community leaders, and parents. Program evaluation was conducted using a descriptive approach based on observation, legal consultation, and a comparison of participants’ knowledge before and after the intervention. The findings indicate a substantial improvement in participants’ understanding of cyberbullying, victims’ rights, reporting mechanisms, and the importance of preserving digital evidence for legal proceedings. The program also revealed limited public awareness of legal protection procedures and identified a cyberbullying case that resulted in psychological distress, social exclusion, disruption of the victim’s right to education, and the need for legal assistance. This community service contributes to strengthening community legal awareness by integrating Indonesian positive law with the Islamic legal principle of ḥifẓ al-'irḍ within maqāṣid al-sharīʿah as a normative foundation for protecting the dignity and rights of cyberbullying victims.